An assessment of the current treatment landscape for rheumatology patients in Qatar: Recognising unmet needs and moving towards solutions. (April 2017) - Emadi, Samar Al; Hammoudeh, Mohammed; Mounir, Mohamed; Mueller, Ruediger B.; Wells, Alvin F.; Sarakbi, Housam Aldeen
Objective: This study assessed the mode of application (oral, intravenous or subcutaneous (SC)) currently employed in the treatment of rheumatoid arthritis (RA) in patients from Qatar in comparison with patients' individual preferences for the mode of application of their treatment. Methods: This study included 294 RA patients visiting three clinics at the main referral hospital in Qatar who were interviewed using a standard questionnaire to determine their preference of mode of application for their disease-modifying antirheumatic drug (DMARD) treatment in relation to their currently employed mode of application. Results: The majority of patients were female (76%), and 93% of male patients and 61% of female patients in the study clinics were of a nationality other than Qatari. The highest patient preference recorded was for an oral therapy (69%), compared with injection (23%) and intravenous (8%) therapy. In total, 85% of patients expressed a preference to remain on oral therapy compared with 63% and 58% of intravenous and SC injection patients indicating a preference to remain on their current method of administration. Conclusions: This high preference for oral therapies highlights the considerable need for incorporation of new oral targeted synthetic DMARD therapies into clinical practice within the region.